Redescription of Chimaera ogilbyi (Chimaeriformes; Chimaeridae) from the Indo-Australian region - Finucci, Brittany; White, William T.; Kemper, Jenny M.; Naylor, Gavin J.p. (Zootaxa, 2018)
An integrated taxonomic approach, combining both morphological and molecular data, was adopted to investigate the Hydrolagus lemures-ogilbyi group in the Indo-Australian region. Single mitochondrial markers (CO1 and NADH2) provided evidence supporting the separation of four distinct species in this group. However, detailed morphological data collected from specimens from across their range failed to find any consistent differences, and many features previously considered to be diagnostic were found to be variable. Nuclear DNA data also failed to support the differences found with the single mitochondrial markers and, together with the morphological data, supported the hypothesis that only a single species in this group is present in the Indo-Australian region. In addition, the results failed to support the current generic placement of this group in Hydrolagus, suggesting they belong to the genus Chimaera with doubt over the validity of Hydrolagus as a valid genus. The oldest available name for this group is Chimaera ogilbyi and a redescription is provided. This species occurs throughout Australia, eastern Indonesia (Java, Bali, and Lombok) and northern Papua New Guinea.